2022
DOI: 10.1098/rsta.2020.0424
|View full text |Cite
|
Sign up to set email alerts
|

The broad edge of synchronization: Griffiths effects and collective phenomena in brain networks

Abstract: Many of the amazing functional capabilities of the brain are collective properties stemming from the interactions of large sets of individual neurons. In particular, the most salient collective phenomena in brain activity are oscillations, which require the synchronous activation of many neurons. Here, we analyse parsimonious dynamical models of neural synchronization running on top of synthetic networks that capture essential aspects of the actual brain anatomical connectivity such as a hierarchical-modular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…We have observed (not shown) similar behavior in small-world networks generated by adding long-range connections and keeping the short-range ones [59]. Other works have also observed dynamical malleability in Kuramoto oscillators coupled under both human-connectome structural networks and hierarchicalmodular networks [19,60]. Additionally, of course, the theory of phase transitions and, consequently, of sampleto-sample fluctuations, is known to apply for a variety of distinct systems.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We have observed (not shown) similar behavior in small-world networks generated by adding long-range connections and keeping the short-range ones [59]. Other works have also observed dynamical malleability in Kuramoto oscillators coupled under both human-connectome structural networks and hierarchicalmodular networks [19,60]. Additionally, of course, the theory of phase transitions and, consequently, of sampleto-sample fluctuations, is known to apply for a variety of distinct systems.…”
Section: Discussionsupporting
confidence: 70%
“…Fixing the coupling strength, we can also look at the distribution of the degree of phase synchronization across samples (purple inset). The magnitude of the sample-to-sample fluctuations peaks during the transitions, at the edge of phase synchronization [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same vein, it was shown in-silico that neuronal avalanches occur at a critical (asynchronous-to-synchronous) phase transition, where they coexist with incipient oscillations (Di Santo et al, 2018). However, while SOC provides a candidate framework for a unified theory of Consciousness (Melloni et al, 2021), a critical state is not strictly required for explaining the presence of spontaneous scale-free neuronal avalanches (e.g., Buendía et al, 2020aBuendía et al, , 2022. For example, it was suggested that during deep sleep or under anesthesia, the brain self-organizes at the edge of bistability (SOB, a first order phase transition Buendía et al, 2020b), rather than SOC (Priesemann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, we also find synchronisation phenomena. Buendía and coauthors provide in The broad edge of synchronisation: Griffiths effects and collective phenomena in brain networks [174] a thorough characterization of the rich dynamical repertoire that arises in brain synchronization when it is combined a minimal dynamical model of neural activity with empirically-observed properties of brain connectivity, such as hierarchical-modular and coreperiphery structures. They reveal the emergence of complex collective states with flexible levels of synchronization, which is a necessary step towards a better understanding of the functional capabilities of brains.…”
Section: Summary Of the Theme Issuementioning
confidence: 99%